FINDING RELATIONSHIP TENDENCY IN ATTACK ON TITAN: LEVI AND ERWIN - Kamila Yasmine Kusuma; Bening Salsa Biela; Vilya Lakstian Catra Mulia (Elite : English and Literature Journal, 2021)
As a popular manga series, Attack on Titan has various characters giving certain impression among the fandom. Two of them are Erwin Smith and Levi Ackerman. Erwin is known as an integrated and influencing commander meanwhile Levi is the humanity's strongest soldier who is also recognized as one of Erwin's closest subordinates. Their togetherness presents questions from the manga fans whether there is special relationship between them. Some fans accepted. However, there are not a few fans refused. Using systemic functional linguistics approach, the researchers try to reveal the happening tendency considering the clauses expressed by these two characters. Doing descriptive qualitative research, tenor analysis is done in the level of grammar. The researchers use criterion-based purposive sampling to get relevant data and process them from domain, taxonomy, componential, up to getting cultural theme analysis. The discussion shows complex interpersonal relationship because of considering the linguistic data findings along with their impacts towards the built social indication. This research gives new perspective for language study towards debatable thing between factions carrying particular ideology.